Investigating Campus Names as an Indispensable Component for University Heritage Conservation and Restoration: A Case Study in China - He , Xubo; Ismail , Nor Atiah; Ismail , Sumarni; Ariffin, Noor Fazamimah Mohd; Yang, Yang (Journal of Ecohumanism, 2024)
Campus names usually carry cultural significance, delivering heritage messages and values as well as basic components of intangible property. One common dilemma regarding university heritage conservation and restoration in the world is arbitrary renaming. This paper aims to justify the inseparable connection between South China Agricultural University (SCAU), South China University of Technology (SCUT), and Sun Yat-sen and develop solutions to their conservation and restoration, taking the Shipai Campus of National Sun Yat-sen University (NSYSU) as a study case. The study concluded that the Shipai campus is the epitome of Sun’s education and it deserves Sun’s name the most. This paper also raised heritage conservation and restoration solutions for SCAU and SCUT, namely identifying the truth and safeguarding historical sustainability by restoring and utilizing the original campus names. In addition, the study proposed to formulate laws for renaming all universities in the future that necessitate deliberate evaluation and approval by heritage experts before taking action. The NSYSU campus serves as a representative case, illustrating the role of campus names as significant cultural property. It highlights the importance of safeguarding campus names. These names must be carefully protected, and arbitrary changes should be avoided to preserve their historical and cultural significance.